Multi-Language Offloading Service: An Android Service Aimed at Mitigating the Network Consumption During Computation Offloading - Matos, Filipe De; Oliveira, Wellington; Castor, Fernando; Rego, Paulo; Trinta, Fernando (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2022: Proceedings of the 28th Brazilian Symposium on Multimedia and the Web, 2022)
Computation offloading has been proposed as an efficient technique to mitigate the computational and energy restrictions associated with mobile devices. Previous work has shown that network latency is a challenge for offloading solutions. In the last years, we have seen continuous improvement in mobile device hardware and studies that have pointed to Java’s poor performance compared to other programming languages. This paper proposes a new Android service, called the Multi-Language Offloading Service, that exploits these two aspects to reduce network consumption and indirectly mitigate the latency problem in an offloading scenario. This service scans the local network searching for binaries of server processes, and executes them on the mobile device itself to handle the requests of the client application locally, without depending on the network. We perform tests with real devices and a Java benchmark application that communicates with Rust server processes via the Apache Thrift framework. The results indicate that, when processing tasks that handle large amounts of data, the service reduces up to forty times the network consumption, 86% the task response time, and 25% the energy use of the mobile device.